Performance Evaluation of PI and Sliding Mode Control for PMSM in Applications for Electric Vehicles - Cherif, Kamel; Sahbani, Abdelaziz; Ben Saad, Kamel (Engineering, Technology & Applied Science Research, 2024)
Electrical and mechanical subsystems are the main parts of the powertrain of an Electric Vehicle (EV). These parts include principally electric motors, inverters, batteries, wheels, axles, differentials, and transmissions. Permanent Magnet Synchronous Motor (PMSM) is one of the most popular used motors in the electric powertrain due to its several benefits over other AC motors, such as its small size, low weight, wide range of speed, elevated overload capacity, elevated power factor, and elevated efficiency. This paper compares the performance of PI and sliding-mode controllers for PMSM employed in electric vehicle applications with single-motor drive configurations. Dynamic performance and robustness are the main topics of the comparative analysis. The robustness of the drive train with sliding-mode controller is proven by simulation results.